(untitled) (Zaporizhzhia Historical Review, 2021)
In the article the data of microlevel researching the peasant family structure of the second half of 18th century have been analyzed. The confession register of Mytchenky village in 1758 is the main source of the research. P.Laslet’s classification of the family households as the most widespread one in the modern historical demography forms the basis of the research as well.